2011
DOI: 10.2528/pierl10110806
|View full text |Cite
|
Sign up to set email alerts
|

Effect on Tumoral Cells of Low Intensity Electromagnetic Waves

Abstract: Abstract-Violations of the process of methylation reveal itself at the early stages of malignant transformation of cells, and the content of 5-methylcytosine can serve as a diagnostic test for tumor formation and treatment of disease. The carried out studies revealed the correlation of antitumor activity of MM-therapy (the use of coherent millimeter electromagnetic waves of low intensity for therapy) with inhibition of methylation of tumor DNA in vivo. It is revealed in our experiments that an half-hour exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…As is well known, low-intensity millimeter and centimeter electromagnetic waves of selective frequencies have a specific therapeutic effect and are therefore widely used in medicine and, in particular, in oncology [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] . Unlike the currently widely used traditional methods of treating tumors with ionizing radiation and chemotherapy, the use of non-ionizing and low-intensity microwaves is devoid of toxic side effects.In Kalantaryan, V.P., et al (2011) [14] it was shown that irradiation of Sarcoma-37 tumor cells with low-intensity non-ionizing and non-thermal millimeter waves at a frequency of 42 GHz suppresses cell growth by 33% and lowers the level of methylation to almost normal. In Kalantaryan,V.P., et al (2020) [15] , on the basis of experimental and theoretical studies, it is concluded that irradiation of tumor tissue at the resonant frequencies of natural vibrations of the molecular structures of water (triads and hexagons) can significantly increase the degree of binding of anticancer drugs to tumor DNA.…”
Section: Introductionmentioning
confidence: 99%
“…As is well known, low-intensity millimeter and centimeter electromagnetic waves of selective frequencies have a specific therapeutic effect and are therefore widely used in medicine and, in particular, in oncology [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] . Unlike the currently widely used traditional methods of treating tumors with ionizing radiation and chemotherapy, the use of non-ionizing and low-intensity microwaves is devoid of toxic side effects.In Kalantaryan, V.P., et al (2011) [14] it was shown that irradiation of Sarcoma-37 tumor cells with low-intensity non-ionizing and non-thermal millimeter waves at a frequency of 42 GHz suppresses cell growth by 33% and lowers the level of methylation to almost normal. In Kalantaryan,V.P., et al (2020) [15] , on the basis of experimental and theoretical studies, it is concluded that irradiation of tumor tissue at the resonant frequencies of natural vibrations of the molecular structures of water (triads and hexagons) can significantly increase the degree of binding of anticancer drugs to tumor DNA.…”
Section: Introductionmentioning
confidence: 99%
“…Among the existing gyro‐devices, gyrotron is a reliable and efficient device to generate powerful EM wave in the frequency range from millimeter‐wave to THz‐wave, which has been applied in many systems . Specifically, the radiation at frequency around 0.1 THz, is drawing the attention of the research community as a potential candidate for cancer treatment, medical treatment, and the security applications . It was reported that a mid‐power gyrotron has been used as a millimeter‐wave source of 95 GHz in some medical application measurements .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Specifically, the radiation at frequency around 0.1 THz, is drawing the attention of the research community as a potential candidate for cancer treatment, medical treatment, and the security applications. [3][4][5][6][7][8][9] It was reported that a mid-power gyrotron has been used as a millimeter-wave source of 95 GHz in some medical application measurements. 8 Reference 9 demonstrates that the radiation around 0.1 THz EM wave could be applied in security applications to detect unusual human behavior.…”
Section: Introductionmentioning
confidence: 99%
“…More and more people want to know whether any confirmed effects have been stated yet [8] and how to overcome the matter without stopping the usage [9][10][11][12][13], resulting in on-going research for decades to analyze the rate of electromagnetic wave being absorbed into a specific averaged mass of tissue of a human body [9,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] and even animals [34][35][36]. The value is obtained by measuring the time rate of RF energy absorption which is given in terms of specific absorption rate (SAR) at various part of body, for example head and hand in the case of mobile phone [20,22,23,25,26,[28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%